A molecularly genetic determination of prognostic factors of the prostate cancer and their relationships to expression of protein p27kip1 - Dvorácková, J; Uvírová, M (Neoplasma, 2007)
Loss of a part of chromosome 8p22, containing the gene LPL and amplifications of the field 8q24 comprising the c-myc oncogene are the most frequent chromosomal aberrations in prostate cancer. We aimed to find the frequency of these chromosomal abnormalities and assess their relationship to the prognosis of prostate cancer patients in relation to Gleason score and expression of p27Kip1. We chose a subgroup of 17 monitored patients who had died during five years following diagnosis, and a group of 31 surviving patients whose Gleason score exceeded 5 (Group of Gleason score 2-3). Owing to lack of tumor cells in puncture biopsies, we made hybridizations in situ and objectively evaluated the result in 35 patients out of 48. Amplification in the field for oncogene c-myc was found in 19 cases (54.2%), in 15 of these (78.9%) polyploidy of the chromosome 8 was also confirmed. Deletion of a part of chromosome 8p22 was found in 21 cases (60%). Normal findings were shown in 8 cases (22.8%) and genetic abnormalities were revealed in 27 patients (77.2%). A Chi-squared test showed the dependence of Gleason score on amplification of the c-myc gene in nonmetastasing prostate cancer. In the case of a Gleason score of group 3, abnormalities in amplification of c-myc were statistically more significant than a Gleason score of group 2 using significance according to the Fisher Exact Probability test (p=0.039). We showed that the level of expression of protein p27 Kip1 was related to abnormality of amplification of the c-myc gene. We also came to the conclusion that decreased expression of protein p27 Kip1 is related the c-myc amplification.
Keywords: Gene Amplification; Immunoenzyme Techniques; hybridizace in situ fluorescenční; protoonkogenní proteiny c-myc; Cyclin-Dependent Kinase Inhibitor p27; Prognosis; Proto-Oncogene Proteins c-myc; mužské pohlaví; nádory prostaty; míra přežití; lidské chromozomy, pár 8; In Situ Hybridization, Fluorescence; imunoenzymatické techniky; prognóza; Prostatic Neoplasms; chromozomální delece; Humans; Survival Rate; Chromosome Aberrations; chromozomální aberace; Chromosome Deletion; inhibitor p27 cyklin-dependentní kinasy; amplifikace genu; Chromosomes, Human, Pair 8; lidé; Male